Throphic ecology of lizard Stenocercus modestus(Squamata: Tropiduridae) in a urban area, Lima, Peru - Pérez Z., José (2012)
The lizard Stenocercus modestusis an endemic specie of coastal desert of the department of Lima, and faces important threats to the conservation of its population. We evaluated the diet of this specie through the analy-sis of the stomach content of 17 individuals. The diet of S. modestusis primarily composed by insects, being the coleopterans, spiders and hymenopterans, the most important eating items. The lizard S. modestuswould present a general diet, judging by the considerable amplitude of its trophic niche.